Impact of Instagram eWOM on Brand Equity and Purchase Intention: A Case Study of Youtfit Customers - Daswan, Muh Irham; Makkulau, Makkulau; Sinarwati, Sinarwati; Daswan, Lestari; Juharsah, Juharsah; Hartini, Hartini (Li Falah: Journal of Islamic Economics and Business, 2024)
The purpose of this study is to determine (1) the influence of Instagram electronic word of mouth (eWOM) on brand equity, (2) the influence of Instagram e-WOM on purchase intention, (3) the influence of brand equity on purchase intention, (4) the influence of brand equity as an intervening variable between eWOM and purchase intention. This study used a simple random sampling technique. The sample in the study was 130 respondents who were Instagram account owners who were friends with the @youtfit__ Instagram account. Data analysis techniques use SEM (Structural Equation Modeling) Analysis analysis. The results showed that Instagram eWOM affects brand equity, Instagram eWOM affects purchase intention, brand equity affects purchase intention, and brand equity acts as an intervening variable between Instagram eWOM and purchase intention on Youtfit.